Ranks of Monoids of Endomorphisms of a Finite Undirected Path - Dimitrova, I. (2020)
In this paper, we study the widely considered endomorphisms and weak endomorphisms of a finite undirected path from monoid generators perspective. Our main aim is to determine the ranks of the monoids wEnd Pn and End Pn of all weak endomorphisms and all endomorphisms of the undirected path Pn with n vertices. We also consider strong and strong weak endomorphisms of Pn.